IDENTIFICATION OF MEDICINAL PLANTS IN THE QUR'AN REVIEWED FROM A SCIENTIFIC PERSPECTIVE - Feby Firmilia Dewi (Al - Mujaddid: Jurnal Ilmu-ilmu Agama, 2023)
In the Al-Qur'an many kinds of plants are mentioned that can be utilized, especially used as medicine. Some of them are olives, pomegranates, ginger, dates, basil, bidara, and cucumbers. Healing a disease using medicinal plants has always been the most prominent in Islamic teachings. The purpose of writing this research is to conduct a literature study regarding the identification of medicinal plants in the Qur'an from a scientific perspective. Several medicinal plants found in the Qur'an contain many active chemical compounds, most of which are antioxidants, anti-inflammatory, antibacterial and anticancer. In addition, drugs derived from natural products or plants do not have side effects, so they are good for treating various diseases.